Complex stenosis morphology and vasomotor responses to inhibition of nitric oxide synthesis. Issue 5 (1st November 2000) - Tousoulis, D; Tentolouris, C; Crake, T; Goumas, G; Stefanadis, C; Toutouzas, P; Davies, G
Abstract : OBJECTIVE: To assess the relation between coronary vasomotor effects of N G -monomethyl-L-arginine (LNMMA) administration and coronary stenosis morphology, length, and severity in patients with stable angina. DESIGN: In 28 patients (24 male, four female) with coronary artery disease and chronic stable angina, intracoronary normal saline and 4 μmol/min LNMMA were infused for four minutes each, followed by an intracoronary bolus of 250 μg glyceryl trinitrate. Coronary stenoses were classified as concentric (smooth), eccentric (smooth), or complicated (irregular). The diameters of these stenoses and their adjacent reference proximal segments were measured by quantitative angiography. RESULTS: During LNMMA infusion a significantly larger proportion of complicated stenoses than concentric and eccentric stenoses constricted by ⩾ 5% (p < 0.01) and the magnitude of vasoconstriction was greater in complicated than in concentric and eccentric stenoses (p < 0.05). For complicated stenoses the magnitude of constriction (in mm) with reference to normal saline was greater than that of the concentric and eccentric stenoses (p < 0.05), whereas concentric and eccentric stenoses constricted similarly. Irrespective of the type of morphology, there was a correlation (p < 0.05) between both the severity and the length of stenoses and the magnitude of vasoconstriction to LNMMA. A similar proportion of concentric, eccentric, and complicated stenoses showed ⩾ 5% increase in diameter with glyceryl trinitrate, and the magnitude of the response was similar in the three groups. CONCLUSIONS: In patients with coronary artery disease, the response to LNMMA is greater when stenosis morphology is complex, indicating greater nitric oxide activity. This provides further evidence that plaques with complex morphology are in an active state.